2006
DOI: 10.1158/1078-0432.ccr-05-1673
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Vascular Permeabilization by Vascular-Targeting Photosensitization: Effects, Mechanism, and Therapeutic Implications

Abstract: Purpose: Loss of vascular barrier function has been observed shortly following vasculartargeting photodynamic therapy. However, the mechanism involved in this event is still not clear, and the therapeutic implications associated with this pathophysiologic change have not been fully explored. Experimental Design: The effect of vascular-targeting photodynamic therapy on vascular barrier function was examined in both s.c. and orthotopic MatLyLu rat prostate tumor models and endothelial cells in vitro, using photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
143
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(153 citation statements)
references
References 32 publications
9
143
0
1
Order By: Relevance
“…With a 24 h drug–light interval, PDT regimens that used low fluence rates were demonstrated to be more successful, with the highest accumulation of fluorescent microspheres occurred within the range of 48–88 J cm –2 and 14–28 mW cm –2 . PDT‐enhanced EPR effects have been shown to be more effective for nanoparticles and large molecules such as dextrans compared to small molecules189, 190, 197 and in this study PDT enhanced accumulation of 0.1 to 2 μm particles while small 0.02 μm particles did not show enhanced accumulation after PDT ( Figure 3 A). PDT improved the tumor uptake of Doxil 2–3‐fold (Figure 3B).…”
Section: Nanoparticle‐mediated Cptsupporting
confidence: 48%
See 2 more Smart Citations
“…With a 24 h drug–light interval, PDT regimens that used low fluence rates were demonstrated to be more successful, with the highest accumulation of fluorescent microspheres occurred within the range of 48–88 J cm –2 and 14–28 mW cm –2 . PDT‐enhanced EPR effects have been shown to be more effective for nanoparticles and large molecules such as dextrans compared to small molecules189, 190, 197 and in this study PDT enhanced accumulation of 0.1 to 2 μm particles while small 0.02 μm particles did not show enhanced accumulation after PDT ( Figure 3 A). PDT improved the tumor uptake of Doxil 2–3‐fold (Figure 3B).…”
Section: Nanoparticle‐mediated Cptsupporting
confidence: 48%
“…PDT has been demonstrated to permeabilize the tumor vasculature and enhance the delivery of nanoparticles 189, 190, 191, 192, 193. The mechanism of PDT‐induced vascular permeabilization is believed to be the direct attack of cytotoxic singlet oxygen generated by PDT, which leads to damage of the vascular endothelial cells and formation of endothelial intercellular gaps 190, 193.…”
Section: Nanoparticle‐mediated Cptmentioning
confidence: 99%
See 1 more Smart Citation
“…Another proposed mechanism is that ROS generated in tumor tissues would form or enlarge the inter-cellular gaps between endothelial cells, leading to enhanced permeability of tumor vasculature. 39) However, no cor-relation was obtained between the size of inter-cellular gaps and the vascular permeability of nanoparticles with different sizes ranging from 100 to 300 nm. 40) Thus, further studies are necessary to elucidate the mechanism(s) behind the enhancement of vascular permeability by PVT and to optimize the treatment for more efficient tumor delivery of subsequently injected nanoparticles.…”
Section: Application Of Photodynamic Treatment To Enhance Tumor Vascumentioning
confidence: 99%
“…In addition to directly killing cancer cells, PDT appears to shrink or destroy tumors in other ways. The photosensitizer can damage blood vessels in the tumor, thereby preventing the cancer from receiving necessary nutrients [17][18][19] . Gomer et al [20] showed that bovine endothelial cells were significantly more sensitive to PDT with porfimer sodium than smooth muscle cells or fibroblasts from the same species.…”
Section: Wwwchinapharcom Tong Zs Et Almentioning
confidence: 99%